DESA BALUNIJUK MENUJU DESA MANDIRI - Maya Yusnita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
Community Service is a form of community service as a manifestation of the practice of the tri dharma of higher education. One of the objectives of the Community Service Program is to train students in applying science, technology, arts and culture as well as developing soft skills and student character. The Universitas Bangka Belitung's X Real Work Lecture in the thematic field held in Balunijuk village aims to provide an understanding of village officials and the local community of the importance of village funds, foster a community entrepreneurial spirit, increase community interest in reading and realize a healthy community through participation in health facilities guaranteed by the government. The implementation method was carried out through surveys, socialization and assistance to residents, which was carried out from July 27 to September 4, 2015. Students were divided into 3 (three) groups according to the main program that has been planned, namely group 1 (socialization of village funds), group 2 (socialization of BPJS health), and group 3 (socialization and entrepreneurship training). The main programs and some additional programs have been carried out well. The addition of BPJS Health membership from the community and the birth of products produced from processed pineapple are benchmarks for achieving the objectives of the Real Work Lecture. This starting point is expected to provide a step forward for Balunijuk village towards an independent village.